Effectiveness of the surgical intervention in the quality of life and survival of patients with metastatic lesions in the spine - Rodrigues,Luiz Cláudio Lacerda (2014)
OBJECTIVE: To evaluate the impact of surgical treatment of metastatic epidural spinal lesions on the quality of life of patients, pain relief and survival. METHODS: Patients with single or double spinal lesions, in good clinical conditions to undergo surgery, were included. Staging and prognostic evaluation were performed, based on imaging studies, according to the criteria of Enneking and Tokuhashi, and neurological status (Frankel), pain (visual analogue scale, VAS) and quality of life index (Oswestry) were also assessed. Survival was calculated. RESULTS: The study included 67 patients, 34 men and 33 women, aged 13-88 years (mean: 53). Most had the breast (23 cases) as the primary site of the tumor and metastasis in the lumbar region, especially in L2 and L3. Pathologic fractures were diagnosed in 45 patients. The mean VAS score was initially 9 (5-10) reducing in the second day after surgery to 2 (1-7) and to 1 (0-6) in the first and sixth months. Following 6 months, 18 deaths were observed (one intraoperatively, five in the first month and 12 at 6 months). The neurological status was correlated with survival: patients who were Frankel E before surgery showed increased survival. CONCLUSION: The surgery does not influence patient survival, except for patients with neurological deficits, who have a worse prognosis. Treatment of metastatic lesions is often palliative, but patients present improved neurological and pain relief and few complications after surgery, justifying surgical intervention.